FOOT-OF-THE-WAVE ANALYSIS OF THE ELECTROCATALYTIC DECHLORINATION OF HEXACHLOROETHANE USING COBALOXIMES - Sebastián Pizarro; Michael Araya; Francisco Gajardo; Darly Concha; Alvaro Delgadillo (Journal of the Chilean Chemical Society, 2019)
In this work the electrochemical degradation of polychlorinated compounds using Co(dmgH)2Cl(py), Co(dpgH)2Cl(py), Co(chgH)2Cl(py) and Co(dbegH)2Cl(py) (where dmgH is dimethylglyoximato, dpgH is diphenylglyoximato, chgH is 1,2-cyclohexanedionedioximato and dbegH is di(4-methylbenzoate)glyoximato) is described. The degradation was studied using cyclic voltammetry by monitoring current changes in the zone near to the Co(II/I) half wave potential as the concentration of the organochloride in the electrochemical cell is increased. Hexachloroethane (HCA) was used as organohalide substrate, while gamma-hexachlorocyclohexane (lindane), 1,2-dichloroethane, and 1,1,1-trichloroethane were used for comparative studies.  The major dechlorination product of HCA, detected through head space GC-MS experiments after bulk electrolysis, was tetrachlorethylene. The rate constants of the dechlorination processes were estimated using the foot-of-the-wave analysis (FOWA), the values obtained were 1.10×105, 2.59×104, 4.91×104   and 1.83×104 for Co(dmgH)2Cl(py), Co(dpgH)2Cl(py), Co(chgH)2Cl(py)  and Co(dpegH)2Cl(py) respectively.